2007
DOI: 10.1016/j.jacc.2007.02.071
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Repolarization Dynamicity Provides Independent Prognostic Information Toward Major Arrhythmic Events in Patients With Idiopathic Dilated Cardiomyopathy

Abstract: In patients with DCM, QT dynamicity is independently associated with the occurrence of major arrhythmic events and improves the predictive accuracy of stratifying arrhythmic risk of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
2
52
3
2
Order By: Relevance
“…A link between inhomogeneous electric depolarization and arrhythmic death in heart failure caused by LV systolic dysfunction has been suggested. 30,31 The present data set demonstrates a significant reduction in prolonged QRS duration (Ͼ120 ms) and QTc dispersion, consistent with a favorable effect on electric remodeling and increased electric stability of the failing left ventricle. Increasing QRS width is associated with advancing age and worsening LV function, 32 whereas CRT would be expected to reduce QRS width; wider QRS intervals are also associated with slower repolarization, in the form of increasing corrected QT interval, and increased dispersion of the QT interval.…”
Section: Electric Instabilitysupporting
confidence: 76%
“…A link between inhomogeneous electric depolarization and arrhythmic death in heart failure caused by LV systolic dysfunction has been suggested. 30,31 The present data set demonstrates a significant reduction in prolonged QRS duration (Ͼ120 ms) and QTc dispersion, consistent with a favorable effect on electric remodeling and increased electric stability of the failing left ventricle. Increasing QRS width is associated with advancing age and worsening LV function, 32 whereas CRT would be expected to reduce QRS width; wider QRS intervals are also associated with slower repolarization, in the form of increasing corrected QT interval, and increased dispersion of the QT interval.…”
Section: Electric Instabilitysupporting
confidence: 76%
“…Pressure-volume (PV) loops were recorded in order to quantify the pacing-induced preload variability, with and without mechanical ventilation, simultaneously with LV MAP, in an additional set of 9 CAVB dogs (median 9 [7][8][9][10][11][12][13][14] weeks after AV-block). In the same experiment, the effect of SAC block by streptomycin on baseline BVR and arrhythmic response to dofetilide was tested; during pacing with alternating PQ, streptomycin was infused (40 mg/kg in 5 min i.v.…”
Section: Quantification Of Preload Variability and Effect Of Sac Blockmentioning
confidence: 99%
“…These results confirm the association between STVMAPD and proarrhythmia, and suggest involvement of the SAC in BVR in the CAVB dog. infusion: 27 vs. 4 [2][3][4][5][6][7][8][9][10][11][12][13] (P=0.07, Figure 6). However, this could not prevent an increase of STVMAPD, from 0.6±0.2 ms to 4.0±3.3 ms (P=0.006), and is similar to the value obtained in the group that received only dofetilide.…”
Section: Streptomycin Abolishes Response Of Bvr To Preload Variation mentioning
confidence: 99%
See 1 more Smart Citation
“…Iacoviello et al (2007) found that NSVT was associated with threefold higher risk of arrhythmic events during follow-up and that prognostic value of NSVT was enhanced by a combination with low LVEF and abnormal QT dynamics. In Marburg Cardiomyopathy study (Grimm, Christ, Bach, Müller, & Maisch, 2003), NSVT evaluated alone was not associated with an increased risk of arrhythmic events; however, when combined with low LVEF, the risk was eightfold higher.…”
Section: Nonischemic Dilated Cardiomyopathymentioning
confidence: 91%